2009
DOI: 10.1007/s11481-009-9145-7
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Expression of Functional Mu Opioid Receptors in Murine Dendritic Cells

Abstract: Opioids are known to exert direct effects on the immune system, and the expression of functional opioid receptors has been reported on several immune cell types. Dendritic cells (DCs) are important inducers and regulators of immune responses. In this study, we investigated whether murine dendritic cells express functional mu opioid receptors (MOR). RT-PCR analysis and double immunofluorescence staining revealed the expression of MOR in activated murine dendritic cells. We also studied the dynamic expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Opposite effects of endomorphins on the release of interleukin-1beta (IL-1β) have been observed, with a inhibitory effect reported in cultured rat peritoneal macrophages [ 29 ], but a stimulatory effect in macrophage cells line THP-1 [ 27 ]. Moreover, previous reports found that endomorphins can inhibit the phosphorylation of p38 MAPK induced by advanced glycation end products in cultured human umbilical vein endothelial cells, and similar results were also found in LPS-stimulated murine dendritic cells [ 30 , 31 ]. These in vitro studies implicate that p38 MAPK and its possible downstream targets inflammatory mediators might contribute to the pain modulation of endomorphins.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…Opposite effects of endomorphins on the release of interleukin-1beta (IL-1β) have been observed, with a inhibitory effect reported in cultured rat peritoneal macrophages [ 29 ], but a stimulatory effect in macrophage cells line THP-1 [ 27 ]. Moreover, previous reports found that endomorphins can inhibit the phosphorylation of p38 MAPK induced by advanced glycation end products in cultured human umbilical vein endothelial cells, and similar results were also found in LPS-stimulated murine dendritic cells [ 30 , 31 ]. These in vitro studies implicate that p38 MAPK and its possible downstream targets inflammatory mediators might contribute to the pain modulation of endomorphins.…”
Section: Introductionsupporting
confidence: 73%
“…In vitro study found that EM-1 could elicit rapid activation of ERK1/2 in rat C6 glioma cells [ 54 ], and morphine induced a decrease of IL-10 and an increase of IL-12 secretion via p38 MAPK pathway in monocyte-derived human dendritic cells [ 55 ]. Furthermore, Li et al found that endomorphins decreased the activation of p38 MAPK induced by LPS, but not that of ERK1/2 in murine dendritic cells [ 30 ]. Therefore, it is possible that the mu-opioid system might have a differential modulation on the activity of p38 MAPK or ERK1/2, depending on cell types, treatments, or in vitro or in vivo studies, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The induced vulnerability of the CNS to infection only exacerbates the increase in neuronal apoptosis observed in the presence of both morphine and gp120 IIIB due to greater p38 MAPK activation (Hu S, 2005). An important factor in the interaction between morphine and immune cells is the presence of the mu-opioid receptor, which is primarily targeted by morphine and is known to be present on DCs (Li Z, 2009). Morphine exposure causes lipopolysaccharide-matured DCs to display an increased T cell stimulatory capacity as well as increased IL-12 production through the p38 MAPK pathway (Messmer D, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review article, Liang et al (2016) developed an overview of how opioids and the immune system interact, suggesting that the EO system plays a direct role on immune system function. They highlight that there is an abundance of research showing that many immune cells have opioid receptors (B€ orner et al, 2009;Li et al, 2009;Wybran et al, 1979), especially MOR receptors (Roy et al, 2006;B€ orner et al, 2013) that directly change immune cell activity. For example, Sarkar et al (2012) have shown that opioids trigger the release of Natural Killer (NK) cells that fight off potential pathogens.…”
Section: Immune System and Endogenous Opioidsmentioning
confidence: 99%